Collection of Handwritten and Old Printed Books of the XVI–XX Centuries and Rare Editions of the Library Yekaterinburg Theological Seminary - P. I. Mangilev; E. A. Poletaeva (Библиосфера)
The article presents the results of studying the collection of rare books and manuscripts of the library of the Yekaterinburg Theological Seminary. The characteristics of the collection and the history of its formation are given. The collection was based on the book fund of the Sverdlovsk Diocesan Administration and books from private donations. The collection of handwritten books includes four copies of the XVI century: the Ostrog Bible and three editions of Andronik Timofeyev Ignorant – Apostle in 1597 and two Octoechos (2nd part) in 1594. There are more than forty editions of the XVII century in the fund: mainly of the Moscow Printing Yard and three “Lithuanian” ones – the “disgraced” teaching Gospel by Cyril Tranquillion, 1619; Synopsis by Innokenty Gizel, 1680; Oktoikh of the second half of the XVII century. The earliest manuscript is the Gospel of 1630-1660, compiled in Galicia, with numerous notes of the owner. The XVIII century is mainly represented by Old Believers’ liturgical and reading (“chetyi”) collections of mixed composition. Collections with canons, akathists, and liturgical charters predominate among the manuscripts of the XIX century. Orthodox written tradition of the XIX–XX centuries is represented by educational literature and musical scores. The result of the research will be the preparation of catalogues of handwritten books of the XVII–XX centuries and books of the old printing of the XVI–XVII centuries from the library collection.